2021
DOI: 10.1002/pol.20210029
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide crosslinker for the enhancement of mechanical properties of polylactic acid

Abstract: Polylactic acid (PLA) biopolymer appears to provide environmental advantages over the petroleum-derived polymers but often ends up with limited applications owing to their poor mechanical performance and brittleness. Herein, we present a PLA polymer compatible graphene oxide (GO) based crosslinker with the intention of improving the mechanical properties. Lactic acid (LA) functionalized GO (GO-LA) crosslinker was prepared and had been crosslinked with the PLA chains through a one-step polycondensation reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 66 publications
(138 reference statements)
0
6
0
Order By: Relevance
“…In contrast, the PLLA-GO surface seems to be smoother, and its morphology is close to the neat PLA. As reported in many papers, it was shown that neat PLA presents a smooth surface compared to filled ones [ 42 , 43 ]. From this result, it is clear that treated GO provides a rough surface to the nanocomposite, which is a characteristic that holds promise for favorable biomedical applications [ 44 ].…”
Section: Resultsmentioning
confidence: 79%
“…In contrast, the PLLA-GO surface seems to be smoother, and its morphology is close to the neat PLA. As reported in many papers, it was shown that neat PLA presents a smooth surface compared to filled ones [ 42 , 43 ]. From this result, it is clear that treated GO provides a rough surface to the nanocomposite, which is a characteristic that holds promise for favorable biomedical applications [ 44 ].…”
Section: Resultsmentioning
confidence: 79%
“…These can be fabricated by mixing GO with natural or synthetic biopolymers, as well as a combination of both to provide specific properties to the final material ( Ege et al, 2017 ; Sayyar et al, 2017 ; Aidun et al, 2019 ; Zhang et al, 2021 ). Although biopolymers are structurally simple molecules, they can covalently bind graphene and other derivatives via cross-linking agents or other physical methods (e.g., high pressure and temperature) ( Sujan et al, 2021 ). Alternatively, GO can interact with biopolymers via weak intermolecular interaction in aqueous buffers.…”
Section: Graphene-based Materialsmentioning
confidence: 99%
“…The GO is one of the promising crosslinking materials to enhance the functionality of nanocomposite hydrogels. 33 Recently, a facile route to prepare a novel functionalized graphene oxide-based crosslinker (GOBC) has been reported in one of the research works. 34 This special crosslinker contains anchored acrylate groups in addition to surface functional species.…”
Section: Introductionmentioning
confidence: 99%